PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KEPUASAN KERJA PEGAWAI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS TADULAKO - Kombong, Agustina (Katalogis, 2015)
The purposes of this research were : 1) to analyze simultaneous effect of work environment and job stress to the job satisfaction of civil servants at Teacher Training and Education Faculty, Tadulako University; 2) to analyze partially the effect of work environment on job satisfaction of civil servants at Teacher Training and Education Faculty, Tadulako University; 3) ) to analyze partially the effect of job stress to the job satisfaction of civil servants at Teacher Training and Education Faculty, Tadulako University. Population of this research covered all the civil servants at Teacher Training and Education Faculty, Tadulako University which consists of 38 civil servants. By considering the number of population is very limited, this study determines all population as the sample using census method. Primary and secondary data have been collected using observation, questionnaire, and documentation. Based on multiple linear regression analysis, the result shows that work environment and job stress simultaneoulysly and partially perform significant effects to the Job Satisfaction of civil servants at Teacher Training and Education Faculty, Tadulako University.